Non-Objectifying Self-Awareness as an Alternative to Naturalistic Psychology in Seseman’s Philosophy - Jonkus, Dalius (Problemos, 2015)
This article analyses objectifying and non-objectifying knowledge in Seseman’s philosophy and how it correlates with self-cognition. Firstly, the critique of the naturalistic psychology is discussed. Secondly, the way Seseman criticizes Moritz Geiger’s concept of the unconscious is analysed. Thirdly, it is examined why a non-objectifying self-consciousness is necessary in the process of self-cognition. The most important result of the distinction of objectifying and non-objectifying cognition is that this distinction allows to make a critical assessment of the limited nature of naturalistic attitude and reveals the dependence of cognition not only on the object’s givenness, but also on the attitude through which it is received. The contemplation of diverse attitudes, the possibility of modifying and combining these attitudes, open up new possibilities to describe the consciousness and the world in which we exist. Through Geiger’s conception of unconsciousness, Seseman reveals that consciousness cannot be reduced solely to conscious experience. However Seseman criticizes Geiger’s concept of the unconscious because it wrongly contrasts consciousness and unconsciousness.
Keywords: phenomenology; non-objectifying self-awareness; naturalistic psychology; Vasily Seseman; Moritz Geiger